"Smart Girl, Good Boy”: Gendered parental messaging, its intergenerational transmission and implications for education and workforce development in The Bahamas - Archer, Lesvie Nicole; Pinder-Darling, Antoinette; Micklewhite, Thalia; Foulkes, Alaina (International Journal of Bahamian Studies, 2025)
This study examines how cultural values shape educational aspirations, influence workforce participation, and inform policy development in The Bahamas. Drawing on data from the Bahamas Cultural Values Survey, it investigates how parental messaging differs by gender and how these values have shifted across three generations. Specifically, the analysis explores whether boys and girls were taught different values, whether these values changed over time, and how they relate to gendered patterns in education and employment. Findings indicate that girls report receiving stronger encouragement in values linked to economic preparedness, social cohesion, and moral instruction, while boys receive less emphasis on academic diligence. This disparity contributes to persistent gender inequalities, with males underperforming in education and entering the workforce with fewer skills aligned to the service-oriented economy. The study highlights the need for further research on the intersection of informal socialization, formal education, and labor outcomes, with particular attention to the role of gender in shaping long-term social and economic cohesion.